Determinasi Kinerja Bank Umum Konvensioanal Di Indonesia - Soekapdjo, Soeharjoto (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
Purpose of this research is to determine the performance of conventional commercial banks in Indonesia. Using monthly time series data from 2014-2018 taken from OJK, BPS, and BI. With regression method a analysis tools and ROA as dependent variable, and independent variable for bank internal factors using CAR, LDR, BOPO, NPL, DPK and macroeconomic factors using inflation, exchange rate, GDP. Result shown that BOPO, inflation, exchange rate have a negative and significant influence to ROA, while LDR, DPK have a positive and significant influence to ROA. For CAR, NPL, Exchange rate and GDP variable, do not have effect to ROA.